Undoing drugs : the untold story of harm reduction and the future of addiction - Szalavitz, Maia (Hachette Go, 2021)
"From "one of the bravest, smartest writers about addiction anywhere" (Johann Hari, New York Times bestselling author)-the untold story of harm reduction, a surprisingly simple idea with enormous power Drug overdoses now kill more Americans annually than guns, cars or breast cancer. But we have tried to solve this national crisis with policies that only made matters worse. In the name of "sending the right message," we have maximized the spread of infectious disease, torn families apart, incarcerated millions of mostly Black and Brown people- and utterly failed to either prevent addiction or make effective treatment for it widely available. There is another way, one that is proven to work. However, it runs counter to much of the received wisdom of our criminal and medical industrial complexes. It is called harm reduction. Developed and championed by an outcast group of people who use drugs and by former users and public health geeks, harm reduction offers guidance on how to save lives and improve health. And it provides a way of understanding behavior and culture that has relevance far beyond drugs. In a spellbinding narrative rooted in an urgent call to action, Undoing Drugs tells the story of how a small group of committed people changed the world, illuminating the power of a great idea. It illustrates how hard it can be to take on widely accepted conventional wisdom- and what is necessary to overcome this resistance. It is also about how personal, direct human connection and kindness can inspire profound transformation. Ultimately, Undoing Drugs offers a path forward- revolutionizing not only the treatment of addiction, but also our treatment of behavioral and societal issues"--